ANALISIS FRAMING MODEL ROBERT N. ENTMAN TENTANG KONFLIK RUSIA DAN UKRAINA PADA MEDIA ONLINE THE WASHINGTON POST DAN XINHUA NEWS - Purwanto Putra; Darra Ananda (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2023)
This article discussed the Framing Analysis of Russian and Ukrainian Conflict News on the online media Xinhua News and The Washington Post April 7, 2022 edition. The study used a constructive paradigm and media representation using the Robert N. Entman Framing analysis method with the assumption that framing had two major dimensions, selection, and emphasis of issues. The study used a qualitative analysis method which aimed to find out how the packaging of news from the Xinhua News and The Washington Post media were opposite each other. The results of the study showed that there were differences in the emphasis on issues in the two online media The Washington Post and Xinhua News. The Washington Post's news framing blamed Russia as a war crime actor for its invasion of Ukraine, while Xinhua News said that the root causes of the conflict between Russia and Ukraine were Russia's continued expansion of the US-led NATO. Keywords: Framing Analysis, Robert N. Entman, Russia-Ukraine Conflict.